AB0484 An Integrated Pharmacokinetic and Pharmacodynamic Approach to Guide Dose Selection of Namilumab, an Anti-GM-CSF Monoclonal Antibody, for Phase II Rheumatoid Arthritis Studies. (9th June 2015) - Wagner, T.; Thienel, U.; Vieser, E.; Souberbielle, B.; Lahu, G.
Abstract : Background: Granulocyte macrophage-colony stimulating factor (GM-CSF) is a soluble cytokine known to play a role in various inflammatory diseases. Namilumab (AMG 203), a human immunoglobulin G1 (IgG1) monoclonal antibody, which potently and specifically neutralises human and macaque GM-CSF, is being developed for the treatment of rheumatoid arthritis (RA) and psoriasis. The selection of an appropriate dosing regimen using modelling and simulation for proof of concept (PoC) studies is a key step in the successful development of pharmaceutics. Objectives: To integrate clinical and non-clinical pharmacokinetic (PK) and pharmacodynamic (PD) data to identify an appropriate subcutaneous dose and dosing regimen for namilumab PoC studies and inform decisions for traditional phase II studies. Methods: In this study we used a multitude of data to build the fundamentals of the analysis. Initially, the effective concentration of 22E9, a surrogate mouse antibody of namilumab, in a collagen-induced arthritis (CIA) mouse model was combined with the outcome of an ex-vivo cellular inhibition assay for namilumab in order to suggest an efficacious concentration range (22E9 and namilumab have similar neutralising potencies against murine and human GM-CSF, respectively). In addition PK/PD similarities and differences of namilumab and anti-TNF-α antibodies, as well as known respective cytokine levels in joints in patients with RA, were used to support the predicted efficacy range of namilumab. These concentrations were translated into human doses using the population PK model developed on data from two phase I studies of namilumab in healthy volunteers (single ascending intravenous doses up to 8mg/kg) and patients with RA (repeated subcutaneous dose study, PRIORA, NCT01317797 ). Results: In the CIA mouse model the EC50 was calculated as 11μg/mL, which was supported by the results of an ex-vivo blood assay. In addition the observation of similar affinities of anti-TNF-α antibodies (12–90pM) and namilumab (46pM), in conjunction with target expression in the synovium in similar ranges of magnitude led to the following conclusion for namilumab: by targeting clinical concentration ranges seen with anti-TNF-α antibodies, this should translate into clinical efficacy. Next, a population PK model was applied to translate clinical concentration ranges into dosing regimens. Hence doses from 20 to 150mg were selected with the intent to cover low, medium and high efficacious exposures in RA and other inflammatory diseases. In addition, a loading dose was suggested for a selected phase II trial, in order to reach steady state faster, thereby supporting an earlier onset of action. Conclusions: Integrating different sources of preclinical and clinical PK and PD information for namilumab and combining these with data from other biologic DMARDs was essential for the selection of namilumab dosing regimens for phase II clinical studies. Disclosure of Interest: T. Wagner Employee of: Takeda Pharmaceuticals International GmBH, U. Thienel Shareholder of: Takeda Pharmaceuticals International, Employee of: Takeda Pharmaceuticals International, E. Vieser Employee of: AMGEN Research GmbH, B. Souberbielle Shareholder of: Takeda Pharmaceuticals International, Employee of: Takeda Pharmaceuticals International, G. Lahu Employee of: Takeda Pharmaceuticals International